Manfaat Literasi Dan Motivasi Belajar Di SD Negeri 6 Saitnihuta, Kec. Pangururan, Kab. Samosir Mahasiswa PkM FKIP UHN Medan - Tigor Sitohang; Yunita Rizky Miranda Sinaga; Delavia Sihombing; Nia Sulastri Br. Gultom; Jenni Maria Sepia Lase; Maria Rahayu Gurning; Hanaria Samosir (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Education is part of a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state. . However, in general, not all education systems in Indonesia become a general benchmark for the surrounding community. There is still a lot of deep concern by the government to care about the education system in Indonesia, especially for schools that are experiencing lagging behind.